Dilucidando la arquitectura genética de la resistencia a múltiples enfermedades de espiga de maíz (Zea mays L.) - Peñas Ballesteros, Andrea; Baricalla, Agustín Ariel; Federico, María Laura; Iglesias, Juliana (Universidad San Francisco de Quito, 2024)
Poster y resumen